A FUNDAMENTAL SUTDY ON DIGITALIZING SALESPERSON BEHAVIOR IN FACE-TO-FACE SALES IN A COSMETICS STORE - MURATA, KOICHI (International Journal of Industrial Engineering: Theory, Applications and Practice, 2018)
Improvement in the service quality of each salesperson has increasingly become a requirement for the growth of the tourist industry in Japan. In order to resolve this problem, the relevant researchers also keep watch on the movement of the digitalization such as Internet of Thing (IoT) and Cyber Physical System (CPS). As one fundamental study on the digitalization of service management in a value chain, this paper proposes a method to visualize the behavior of a salesperson in face-to-face sales by adopting an industrial-engineering approach. This allows the development of a network diagram to represent complicated service processes for multiple customers by one salesperson. A quantification of the processes is also performed to identify characteristics of the customer-service behavior for a particular salesperson by three developed indicators based on the data of the created diagram. In addition, an application study is performed to confirm the utility of the proposed methods in the case of a cosmetics shop. The results obtained provide the detail perspective to digitalize the current state of the customer service process of the analyzed salesperson, allowing for rapid improvement of their service quality.